REASSESSING THE EFFECTIVENESS OF AL-GHAZALI BASED COUNSELING: A Spiritual Approach to Addressing Diverse Client Challenges - Yarmis Syukur; Ahmad Wahid; Triave Nuzila Zahri; Zuhri Arif; Syah Wardi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
Al-Ghazali’s counseling framework offers a spiritually grounded alternative within contemporary Islamic psychotherapy. Despite its intellectual depth, empirical discussions of its effectiveness remain limited compared to dominant Western counseling models. This study seeks to synthesize recent scholarly evidence on the effectiveness of Al-Ghazali–based counseling in addressing various client concerns. Employing a systematic literature review guided by the PRISMA protocol, the study analyzed ten peer-reviewed articles published between 2020 and 2025 and indexed in Scopus. The findings indicate that this spiritually oriented approach demonstrates promising outcomes in reducing maladaptive thinking patterns, managing anger, preventing substance misuse, and supporting mental health recovery. Beyond symptom reduction, it fosters moral awareness and inner balance. The study concludes that Al-Ghazali’s counseling model holds significant therapeutic potential and warrants further development across diverse cultural and clinical contexts.